Kinetic oscillations in the NO+CO reaction on the Pt(100) surface: an alternative reaction mechanism - Alas, S. J. (2005)
Kinetic oscillations in the catalytic reduction of NO by CO on a reconstructing Pt(100) surface are simulated by using a dynamic Monte Carlo method. The simulation is based on the HS model and takes into account an alternative reaction mechanism arising from recent experimental findings for the catalytic reduction of No on Rh(111), which replaces the classical N+N recombination step by the formation of a (N–NO)∗ intermediary species for the production of molecular nitrogen. A synchronized mechanism and spatiotemporal patterns are observed during the oscillations. Oscillations are analyzed in terms of the controlling parameters involved in the reaction mechanism. Different values of these parameters lead to sustained, attenuated, and modulated oscillations.